PERAN DEWAN KOMISARIS INDEPENDEN MEMODERASI PENGUNGKAPAN CSR TERHADAP KINERJA KEUANGAN - Nuraini, Annisa; Machmuddah, Zaky (Proceeding SENDI_U, 2021)
This study aims to determine the relationship between financial performance, corporate social responsibility, and good corporate governance (GCG). CSR is measured based on the GRI (Global Reporting Initiatives) standard indicators. Financial performance is measured by using the rate of return on assets (Return on Assets). Meanwhile, the indicators used in GCG are the proportion of independent commissioners and the number of audit committees, the sample used in this study was 15 agricultural companies listed on the Indonesia Stock Exchange in 2016-2019 with purposive sampling. The analysis tool uses Warp PLS 5.0. The test results prove that CSR has a positive effect on financial performance, GCG which is proxied by the portion of the independent board of commissioners can moderate CSR on financial performance, however, the number of audit committees cannot moderate CSR on financial performance. The implication of this research is the importance of CSR disclosure to improve the company's financial performance.